FORMATION OF READING CULTURE IN PRESCHOOL EDUCATION: THE ROLE OF FAMILY AND EDUCATORS - Tuychiyeva Zulfizar Boxodir qizi (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article explores the formation of reading culture in preschool children, emphasizing the significant role of both family and educators. Developing a reading culture at an early age contributes to children’s cognitive, emotional, and social development. The study analyzes effective strategies and cooperation between parents and teachers in fostering reading habits among preschoolers. Practical recommendations for strengthening family-educator partnerships are also provided.